Valuing Florida’s Water Resources: Ecosystem Services Approach - Tatiana Borisova; Tara Wade; Xiang Bi; Kurt Oehlbeck; Kelly A. Grogan (EDIS)
This 6-page fact sheet written by Tatiana Borisova, Tara Wade, Xiang Bi, Kurt Oehlbeck, and Kelly Grogan and published by the UF/IFAS Food and Resource Economics Department defines the term “ecosystem services” and presents examples of ecosystem services provided by water resources. It explains three values people assign to water resources and presents a brief overview of the methods that economists employ to measure the value of water. https://edis.ifas.ufl.edu/fe1064